Dynamic Analysis and Fatigue Life Evaluation of Single Herringbone Planetary Gear System with Crack Fault - Sheng, Dongping; Yang, Jie; Su, Chun (Universitas Negeri Malang, 2025)
The herringbone planetary gear transmission is widely used due to its exquisite compact structure, excellent load-bearing capacity, and stable transmission characteristics. However, root crack is one of the most common failure modes of gears. A cracked herringbone planetary gear system is taken as research object. The sun gear with crack fault is studied from the aspect of modal and transient dynamic analysis, and the related results are compared with the healthy gear. Based on the transient dynamic analysis of the herringbone teeth with cracks, a fatigue life evaluation is conducted. Firstly, the results show that no significant difference between the natural frequencies and main vibration modes of healthy gears and faulty gears could be observed. Secondly, through transient dynamic analysis, it can be found that, during the rotation process of gears and with the increase of crack depth, the stress at the crack area increases gradually. As the crack penetration length increases, the stress at the crack endpoint of the gear increases almost linearly. Additionally, by comparing cracks with different depths and penetration lengths, the depth of the crack has a greater impact on the stress of the gear compared to the crack penetration length. Finally, based on the fatigue life analysis, the depth of the crack has a significant impact on the gear life; even if the depth of the crack is not very large, it will still have a significant impact. The related research is valuable and could guide the design and optimization of herringbone planetary gear system from the point of practical application.